DEVELOPMENT OF A NEW STABILITY INDICATING RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF EPALRESTAT AND PREGABALIN AND ITS VALIDATION AS PER INTERNATIONAL CONFERENCE ON HARMONIZATION GUIDELINES - Goday, Swapna; Sk, Abdul Rahaman; A, Prameelarani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was aimed to develop a novel, simple, rapid, accurate, stability-indicating reversed-phase high-performance liquid chromatography method, and validate for the simultaneous estimation of epalrestat and pregabalin in bulk and dosage form. Methods: The chromatographic separation was performed on c18 column discovery (250 mm × 4.6 mm, 5 μ particle size) the optimized mobile phase consists of 0.01 m potassium dihydrogen phosphate buffer: Methanol (25:75% v/v) with a flow rate of 1.0 ml/min and ultraviolet (UV) detection at 226 nm. Results: The chromatographic condition, retention time was 2.2 min (pregabalin), 2.8 min (epalrestat). Stress testing was performed in accordance with an International Conference on Harmonization (ICH) Q1A R2 guidelines. The method was validated as per ICH Q2 R1 guidelines. Linearity range was 30–180 ppm (epalrestat), 15–90 ppm (pregabalin), accuracy was in the range of 98.14–100.43% for both the drugs. Precision was 0.2% and 0.3% for epalrestat and pregabalin. Limit of detection and limit of quantification are 0.21 μg/ml and 0.65 μg/ml for epalrestat and 0.08 μg/ml and 0.25 μg/ml for pregabalin. Conclusion: The method developed is more sensitive, accurate, and precise than the methods reported earlier. Retention time and runtime were also less, and hence, the method is economical. When applied for tablet assay, drug content was within 100.06–100.22% of the labeled content. Forced degradation studies indicated the suitability of the method for stability studies. The proposed method can be used for routine determination of epalrestat and pregabalin.